Differences in Neuropathic Pain and Radiological Features Between AQP4-ON, MOG-ON, and IDON - Kang, Hao; Qiu, Huaiyu; Hu, Xiaofeng; Wei, Shihui; Tao, Yong (Frontiers in Pain Research, 2022)
Purpose The purpose of this study was to investigate pain and radiological features of different types of first-episode demyelinating optic neuritis (ON). Methods Eighty-three patients presenting with first-episode aquaporin-4 (AQP4) antibody-associated ON (AQP4-ON; n = 28), myelin oligodendrocyte glycoprotein (MOG) antibody-associated ON (MOG-ON; n = 26) and idiopathic demyelinating optic neuritis (IDON, n = 29) were included in this retrospective case-control study. We assessed optic nerve lesions on magnetic resonance imaging (MRI), acute pain associated with onset of optic neuritis and clinical characteristics of those ON patients with different serum autoantibody status. Results 24 AQP4-ON patients (85.75%), 23 MOG-ON patients (88.5%) and 24 IDON patients (82.8%) suffered from ON-associated pain. MOG-ON had mostly retro-orbital pain; AQP4-ON and IDON had mostly neuropathic pain. In addition, pain was more severe in AQP4ON patients than in other ON patients. In MRI, bilateral involvement was more common in AQP4-ON than IDON (26.9 and 3.7%); radiological optic nerve head swelling was more common in MOG-ON than in AQP4-ON and IDON (68.0 vs. 23.1 vs. 25.9%). MRI lesion in peri-optic nerve sheath was more common in AQP4-ON (53.8 vs. 16.0 vs. 3.7%). In 70 patients with ON-associated pain, gadolinium enhancement of orbital optic nerve was most common in MOG-ON patients (82.4 vs. 55.0 vs. 33.3%, P = 0.018), and enhancement of optic chiasma was most common in AQP4-ON patients (40.0 vs. 5.9 vs. 6.7%, P = 0.015). Perineural and orbital enhancement was observed only in patients with MOG-ON (P < 0.001). The length of enhancement was longer in AQP4-ON patients than in MOG-ON and IDON patients. Conclusion Pain is a common symptom in patients with all types of demyelinating ON. AQP4-ON is frequently associated with severe ON-associated pain and longitudinally extensive optic nerve inflammatory lesions. Intra-orbital and peri-optic inflammation were more frequently observed in patients with MOG-ON, which was closely related to optic disc swelling and retro-orbital pain provoked by eye movements.